2008
DOI: 10.1073/pnas.0709115105
|View full text |Cite
|
Sign up to set email alerts
|

A human mutation in Phox2b causes lack of CO 2 chemosensitivity, fatal central apnea, and specific loss of parafacial neurons

Abstract: Breathing is maintained and controlled by a network of neurons in the brainstem that generate respiratory rhythm and provide regulatory input. Central chemoreception, the mechanism for CO2 detection that provides an essential stimulatory input, is thought to involve neurons located near the medullary surface, whose nature is controversial. Good candidates are serotonergic medullary neurons and glutamatergic neurons in the parafacial region. Here, we show that mice bearing a mutation in Phox2b that causes conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
331
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 283 publications
(376 citation statements)
references
References 52 publications
27
331
2
3
Order By: Relevance
“…First, neurons of the adult rat RTN, defined physiologically by their responsiveness to CO 2 in vivo (Mulkey et al 2004;reviewed in Guyenet 2008), and phenotyped as Vglut2 þ (but negative for glutamate decarboxylase and tyrosine hydroxylase) and located at the ventral medullary surface under the facial nucleus and extending approximately 500 mm caudal to it, were all found to express Phox2b (Stornetta et al 2006). Second, inspection of the hindbrain of Phox2b 27Ala/þ newborn mice that have no response to hypercapnia ( §2) showed that there was an 85 per cent depletion of the Phox2b þ /Vglut2 þ RTN neurons (Dubreuil et al 2008). This observation held true for embryonic day (E)15.5 embryos, ruling out post-natal hypoxic injury as a cause.…”
Section: Mutations In Phox2b and The Drive To Breathementioning
confidence: 99%
See 2 more Smart Citations
“…First, neurons of the adult rat RTN, defined physiologically by their responsiveness to CO 2 in vivo (Mulkey et al 2004;reviewed in Guyenet 2008), and phenotyped as Vglut2 þ (but negative for glutamate decarboxylase and tyrosine hydroxylase) and located at the ventral medullary surface under the facial nucleus and extending approximately 500 mm caudal to it, were all found to express Phox2b (Stornetta et al 2006). Second, inspection of the hindbrain of Phox2b 27Ala/þ newborn mice that have no response to hypercapnia ( §2) showed that there was an 85 per cent depletion of the Phox2b þ /Vglut2 þ RTN neurons (Dubreuil et al 2008). This observation held true for embryonic day (E)15.5 embryos, ruling out post-natal hypoxic injury as a cause.…”
Section: Mutations In Phox2b and The Drive To Breathementioning
confidence: 99%
“…Transmitting chimeras produced heterozygous pups (Phox2b þ/27Ala ) that died soon after birth from respiratory failure (Dubreuil et al 2008). Plethysmography performed prior to death revealed an absence of response to hypercapnia.…”
Section: Mutations In Phox2b and The Drive To Breathementioning
confidence: 99%
See 1 more Smart Citation
“…In mice carrying a Phox2b mutation that causes the human congenital central hypoventilation syndrome (13), all Task2-positive RTN neurons were lost. In plethysmography and in vitro en bloc preparation, Task2 −/− mice showed compromised central respiratory adaptation to hypoxia and hypercapnia.…”
mentioning
confidence: 99%
“…Recently, a mouse model that carries a mutation of the transcription factor Phox2b, which causes congenital central hypoventilation syndrome in humans, was engineered. A specific loss of a population of Phox2b-expressing RTN/pFRG neurons was associated with early death of these newborn mice due to the lack of the ventilatory response to hypercapnia (13).…”
mentioning
confidence: 99%